Arus Kas Bebas, Keputusan Pendanaan, Insider ownership, dan Kebijakan Dividen - Annisa Barokatuh Rahman; Putri Nurmala (JAAF (Journal of Applied Accounting and Finance), 2023)
This study endeavors to examine the impact of free cash flow, funding decisions, and insider ownership on dividend policy, focusing on companies in the cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) during the period 2017-2021. The research adopts a quantitative approach employing purposive sampling techniques. Secondary data from annual financial reports, available on the Indonesia Stock Exchange (IDX) for the specified period, forms the basis of the analysis. Six companies are selected as samples for a five-year research period, resulting in 30 observations. The data is processed using panel data regression analysis to test the hypotheses. The findings from the t-statistic tests (partial tests) reveal the following: Firstly, free cash flow, when considered independently, exerts a positive and significant influence on dividend policy. Secondly, funding decisions, when analyzed in isolation, demonstrate a negative and significant impact on dividend policy. Lastly, insider ownership, when examined partially, exhibits a positive and significant association with dividend policy.